Coronary and myocardial metabolic effects of combined glyceryl trinitrate and propranolol administration. Observations in patients with and without coronary disease. - Schang, S J (1978)
Coronary haemodynamic and metabolic effects of propranolol and glyceryl trinitrate were studied in 12 patients with coronary artery disease and 5 without coronary heart disease, at rest and during tachycardia stress. Propranolol-associated reductions in indices of myocardial oxygen demand, left ventricle work, tension time, and left ventricle oxygen utilisation (LVVO2) were reversed when heart rate was controlled by atrial pacing. Adding glyceryl trinitrate at rest also restored heart rate but decreased the left ventricular work index and tension time index as coronary resistance declined paradoxically. Tachycardia-related increases in tension time index and LVVO2 were unchanged after propranolol, and ischaemia (angina, ST depression, and reduced lactate extraction) was not altered in most of the patients. During tachycardia, the addition of glyceryl trinitrate decreased the tension time index and LVVO2; angina recurred in only 4 patients, and ST depression and lactate extraction improved. Similar haemodynamic changes occurred in the patients with normal coronary arteries. In contrast with propranolol administered alone, propranolol plus glyceryl trinitrate enhances tachycardia tolerance and prevents tachycardia-induced manifestations of ischaemia. This action is attributed to glyceryl trinitrate-associated improvement in the adequacy of myocardial perfusion.